ANALYSIS ON THE EFFECT OF IRRIGATION ON SELECTED VEGETABLES PLANTED AROUND ZOBE DAM, DUTSIN-MA - Kabo, Kamaluddeen Suleiman; Albashir, Yasir; Saulawa, Abdulmalik; Muhammad, Abdullahi; Yusha’u, Auwal; Shema, Abdulsalam Shehu; Bello, Ja'afaru; Bello, Abdu Muhammad (FUDMA JOURNAL OF SCIENCES, 2023)
Agricultural soil pollution through irrigation with polluted water is one of the major sources of soil pollution and accumulation of heavy metals in soils and plants. The purpose of this study was to determine the concentration of heavy metals (Pb and Cr) in soil and vegetable sample in tomato, spinach and pepper, planted around Zobe Dam, during wet and dry season, using Atomic Absorption Spectrophotometer. Results obtained from this study showed overall concentration of heavy metals (Pb and Cr) respectively, in the range (0.000-2.309) and (0.000-0.204) ppm in the vegetable sample. Generally, the concentration of (Pb) were higher in wet season than the dry season, ranging from (0.000-2.309) ppm and (0.000-0.129) ppm respectively. So also, (Cr) was only detected in one sample P1b (pepper dry season). Whereas, concentration of these metals where not detected in all the soil samples. Similarly, it was found that the concentration of these metals were found to be higher during the wet season with the highest concentration of (Pb) recorded during the wet season. Concentration of (Pb) during the wet season was found to be higher than the WHO recommended value in the vegetable samples.